"Honestly, Anywhere that I Have Wi-Fi": A Posthuman Approach to Young Women's Activist Blogging. Issue 2 (1st June 2022) - Sheppard, Lindsay C.; Raby, Rebecca
Abstract: We add to the scholarship on young women's online activism using a Baradian framework to explore the material-discursive contexts that co-create the meanings and possibilities of their activism. Through a diffractive methodology, we delve into key moments from blogs and interviews with bloggers to discuss two emerging themes. First, we offer an understanding of activist girl blogger subjectivities as intra-actively embedded and remade in material-discursive contexts of girlhood, artist, and celebrity in a neoliberal digital culture that valorizes social media influencers. Second, we examine the related entanglements of discourses-materialities-time-space-bodies, and the human and non-human agencies that co-constitute young women's activist blogging. Overall, we illustrate the potential of a Baradian approach for understanding the human and more-than-human complexities of young women's activist blogging and activist subjectivities.